MULTIPLE TACTICS OF INTEGRATED PEST MANAGEMENT FOR THRIPS ON STRAWBERRY PLANTATION - Mudjiono, Gatot; Prasman, Yahya; Afandhi, Aminudin (AGRIVITA, Journal of Agricultural Science, 2015)
In management of thrips on strawberry, farmers usually use synthetic insecticides. Synthetic insecticide is not effective to control thrips and produce residual effect on crops. Insecticidal residue is dangerous for human, natural enemies and environment widely. Therefore, it is necessary to find an alternative thrips pest control on strawberries, through integrated pest manage-ment (IPM) implementation. Research was aimed to determine the effect of IPM technology for Thrips sp. on strawberry plantation. Research was conducted on strawberry plantation by comparing IPM and conventional plots, in Kusuma Agrowisata Batu from April to July 2009. Variables were used such as the number of larvae, adult population and damage intensity caused by Thrips sp., and fruit production. Data was analyzed by t-test on 5%. The results showed that the average larva and adult population of Thrips sp. on IPM plot were higher than conventional plot, 1.12 and 0.50 for larva and 0.87 and 0.27 for adults respectively. The damage intensity of strawberry crops on IPM plot was higher than conventional plot, 11.69 and 5.98% respectively. Based on average fruit production, IPM plot was higher than conventional plot, 48.32 g and 39.24 g respectively.Â Keywords: damage intensity, fruit production, IPM, strawberry, Thrips sp.